A microwave energy meter to estimate energetic reserves in juvenile sturgeon. (28th February 2022) - Djokic, Matea A.; Heishman, Joshua; Kappenman, Kevin M.; Gaylord, T. Gibson; Verhille, Christine E.
Abstract: Energetic stores can be metrics of fish health but are determined using lethal methods. Validation of non‐lethal alternatives to estimate energetic stores would facilitate monitoring of wild fish of conservation concern, such as sturgeons. The Distell Fatmeter, a microwave energy meter, has been validated to estimate energetic reserves in a range of fish taxa but has not been tested on sturgeon. Therefore, Fatmeter measurements were tested as a predictor of captive hatchery‐origin juvenile pallid sturgeon (fork length: 240–415 mm) energetic reserves determined by lethal proximate analysis. Fatmeter measurements combined with size and condition metrics accounted for 40 to 45% of the variation in whole‐body energetic reserves, which is notably lower than reported in previous studies on other fish taxa and a modest improvement on variation explained by size and condition metrics alone in the same sturgeon population. We suggest the low variation accounted for by the Fatmeter may be a result of small body size and low whole‐body lipid content and recommend follow‐up studies on sturgeon larger than 415 mm in fork length.